Mechanism of Zinc Excitotoxicity: A Focus on AMPK - Kim, Yang-Hee; Eom, Jae-Won; Koh, Jae-Young (Frontiers in Neuroscience, 2020)
Over the last 20 years, it has been shown that complex signaling cascades are involved in zinc excitotoxicity. Free zinc rapidly induces PKC activation, which causes ROS production at least in part through NADPH oxidase. It also promotes neuronal nitric oxide synthase, thereby increasing NO production. Erk1/2 activation and Egr-1 transcription factor activity were quickly induced by zinc, too. These concurrent actions of kinases consequently produce oxygen free radical, ROS, and NO, which may cause severe DNA damage. Following the excessive activity of poly(ADP-ribose) polymerase-1 depletes NAD+/ATP in the cells. Zinc excitotoxicity exhibits distinct characteristics of apoptosis, too. Activation of caspase-3 is induced by liver kinase B1 (LKB1)-AMP-activated kinase (AMPK)-Bim cascade signaling and induction of p75NTR receptors and p75NTR-associated Death Executor. Thus, zinc excitotoxicity is a mechanism of neuronal cell death showing various cell death patterns. In addition to above signaling cascades, certain intracellular organelles also play a key role in zinc excitotoxicity. Mitochondria and lysosomes function as zinc reservoirs, and as such, are capable of regulating zinc concentration in the cytoplasm. However, when loaded with too much zinc, they may undergo mitochondrial permeability transition pore opening, and lysosomal membrane permeabilization, both of which are well-established mechanisms of cell death. In this paper, we discussed our more recent findings about the role of AMPK in zinc excitotoxicity. LKB1 is upstream kinase for AMPK, and Bim, one of the pro-apoptotic Bcl-2 family members, is a downstream mediator for zinc-induced caspase-3 dependent apoptosis. Since zinc excitotoxicity has been reported to be associated with acute brain injuries, we performed to find the novel AMPK inhibitors as therapeutic agents for these diseases. We tried to see the neuroprotection against zinc excitotoxicity, calcium-overload excitotoxicity, oxidative damage, and apoptosis because we thought acute brain injury has complicated neuronal death pathways. We selected two chemical candidates and observed neuroprotection against brain damage in the animal model of stroke. In this review, we introduced the AMPK-mediated cell death mechanism and novel strategy for the development of stroke therapeutics. The hope is that this understanding would provide a rationale for acute brain injury and eventually find new therapeutics.